IMPLEMENTATION OF REGENT REGULATION NUMBER 7 OF 2015 CONCERNING GUIDLINES FOR ADVERTISEMENT TAX COLLECTION - Ita Ainul Khasanah; Aloysius Rengga (Journal of Public Policy and Management Review, 2019)
Billboard tax is a tax on billboards. Billboards are objects, tools, deeds, or media whose various forms and features are designed for the purpose of commercially introducing, encouraging, promoting, or to draw public attention to goods, services, people, or bodies, which can be seen, read, heard, felt, felt, and / or enjoyed by the public. This study aims to evaluate the impact of advertisement tax on local revenue and to analyze the obstacles faced by related agencies in carrying out advertisement tax collection. This study uses descriptive qualitative research methods conducted through interviews with several informants selected using purposive sampling techniques. The results showed that the impact of advertisement tax on local revenue in the district of Demak was not optimally influenced by the lack of socialization that covered all taxpayers, causing the discovery of illegal billboards both those that had not taken care of licensing or had not paid taxes. That is because there are obstacles, namely the lack of communication between agencies related to taxpayers and the unavailability of staff / employees who specifically manage advertisement tax. The recommended recommendation is to increase the socialization that has been done so far and cover all taxpayers and increase the number of staff in managing advertisement tax in according to his ability.